2014
DOI: 10.1038/ncomms5525
|View full text |Cite|
|
Sign up to set email alerts
|

Force-dependent conformational switch of α-catenin controls vinculin binding

Abstract: Force sensing at cadherin-mediated adhesions is critical for their proper function. α-Catenin, which links cadherins to actomyosin, has a crucial role in this mechanosensing process. It has been hypothesized that force promotes vinculin binding, although this has never been demonstrated. X-ray structure further suggests that α-catenin adopts a stable auto-inhibitory conformation that makes the vinculin-binding site inaccessible. Here, by stretching single α-catenin molecules using magnetic tweezers, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
482
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(504 citation statements)
references
References 73 publications
19
482
1
2
Order By: Relevance
“…Its activation and recruitment to force-activated talin (and likely to ␣-catenin) involve phosphorylation and allosteric interactions with cytosolic binding partners (34,61,63,64). Conversely, recent experimental data demonstrated that force directly activates ␣-catenin (30,42), and the present simulations suggest that this occurs by a process involving salt-bridge disruption within the M region. Despite sharing a core structural motif, these proteins differ in their activation mechanisms, functional binding partners, and roles in force transduction.…”
Section: Salt-bridgesmentioning
confidence: 45%
See 1 more Smart Citation
“…Its activation and recruitment to force-activated talin (and likely to ␣-catenin) involve phosphorylation and allosteric interactions with cytosolic binding partners (34,61,63,64). Conversely, recent experimental data demonstrated that force directly activates ␣-catenin (30,42), and the present simulations suggest that this occurs by a process involving salt-bridge disruption within the M region. Despite sharing a core structural motif, these proteins differ in their activation mechanisms, functional binding partners, and roles in force transduction.…”
Section: Salt-bridgesmentioning
confidence: 45%
“…Recent single protein unfolding studies reported the forced unfolding of MI-MIII when stretched along the N-to-C-terminal axis (42). The protein appeared to unfold in three sequential steps in which an initial unfolding event at ϳ5 pN appeared to expose the VBS in MI, while retaining the structures of MII and MIII.…”
mentioning
confidence: 99%
“…4 Although the cadherin-catenin complex is commonly described as the 'core' VE-cadherin complex, many other proteins can associate, such as scaffolding proteins and cytoskeletal regulators. 3,5 Some of these proteins, including vinculin, [6][7][8][9][10][11] epithelial protein lost in neoplasm (EPLIN) 12,13 a-actinin 14 and afadin, 15,16 have been found to bind to both a-catenin and actin and are therefore suggested to act as a link between the cadherin-catenin complex and actin. However, biochemical studies showed that a minimal cadherin-catenin complex consisting of E-cadherin, b-catenin and aE-catenin can directly bind to filamentous actin (F-actin).…”
Section: Introductionmentioning
confidence: 99%
“…17 Interestingly, binding of vinculin to aEcatenin has also been demonstrated to be stabilized by tension. 18,19 In endothelial cells, force exerted on cell-cell junctions was shown to recruit vinculin, which protected VE-cadherin junctions against opening. 11 Together, these data suggest that tension on junctions may promote binding of cadherin/b-catenin as well as vinculin to a-catenin, resulting in their re-enforcement and growth.…”
Section: Introductionmentioning
confidence: 99%
“…This can finally lead to the activation of chemical signaling cascades. As discussed in Yap (2017), AJs function as mechanosensors (Huveneers and de Rooij 2013;Yao et al 2014;Ladoux et al 2015;Muhamed et al 2016), whereas a role in force sensing has so far not been attributed to desmosomes. At the same time, desmosome-mediated intercellular adhesion is much stronger than AJmediated cohesion as shown by the epithelial sheet assay: Whereas depletion of the desmosomal plaque component plakophilin 1 (PKP1) in keratinocytes disrupts epithelial cohesion on application of mechanical stress, knockdown of the corresponding components from AJs, p120, or p0071/PKP4, has no immediate effect on intercellular cohesion (Fig.…”
mentioning
confidence: 99%